Sub-regional variability in the influence of ice-contact lakes on Himalayan glaciers - Alex C. Scoffield; Ann V. Rowan; Duncan J. Quincey; Jonathan L. Carrivick; Andrew J. Sole; Simon J. Cook (Journal of Glaciology)
Ice-contact lakes modify glacier geometry and dynamics by shifting the majority of mass loss from the ice surface to the terminus. Lake-terminating glaciers are known to experience greater thinning rates and higher velocities than land-terminating glaciers, but the controls on variability in surface elevation change and ice flow between lake-terminating glaciers in different regions remain poorly explored. We combined existing datasets of glacier velocity, surface elevation change and glacial lake area to characterise the evolution of 352 lake-terminating and land-terminating glaciers within three Himalayan sub-regions between 2000 and 2019. These analyses show that the influence of ice-contact lakes propagates up-glacier across only the lowermost 30% of the hypsometric distribution, even where lakes are well established. We find that ice-contact lakes only affect glacier behaviour when the lakes reach an advanced evolutionary stage; most clearly manifested in the Eastern Himalaya by statistically robust differences in glacier-wide surface elevation change between lake-terminating (–0.68 ± 0.05 m a–1) and land-terminating (–0.54 ± 0.04 m a–1) glaciers. These differences are driven by the presence of a greater number of well-developed ice-contact lakes in the Eastern Himalaya compared to in the Western and Central Himalaya, resulting from greater mass loss rates to date.